Improving Biosecurity Procedures to Minimize the Risk of Spreading Pathogenic Infections Agents After Carcass Recycling - Pandey, Pramod; Vidyarthi, Sriram K.; Vaddella, Venkata; Venkitasamy, Chandrasekar; Pitesky, Maurice; Weimer, Bart; Pires, Alda F. A. (Frontiers in Microbiology, 2020)
Animal proteins are essential elements of human and animal feed (HAF) chain and improving the HAF safety requires understanding and controlling of the transmission of infectious agents in food chain. Many pathogenic infectious agents, such as prion protein is known to damage the central nervous system in the cattle. Bovine spongiform encephalopathy (BSE) results from infection agent (prion), and affects number of species such as cattle, human, and cats. In addition, Salmonella, pathogenic E. coli O157:H7, and Listeria monocytogenes were found in animal by-products used in the HAF production. Increased interest in controlling microbial risks in HAF is evidenced by a large number of publications, which highlights the need for examining the animal disposal method such as rendering process and provides a broader perspective of rendering process. While existing practices help greatly in controlling microbial contamination, this overview study showed that additional biosafety measures are necessary to ensure microbial safety in animal feed.